Variability of morphological features and nuclear DNA content in haploids and doubled haploids of androgenic callus lines of rice (Oryza sativa L.) - M. V. Ilyushko; M. V. Skaptsov; M. V. Romashova (Труды по прикладной ботанике, генетике и селекции)
The work is relevant for understanding evolutionary processes in plant species. Twelve callus lines with multiple regeneration of haploids and doubled haploids were obtained in F1 hybrids of Oryza sativa L. through in vitro androgenesis. Intracallus variability of the morphological features of haploids was often accompanied by a decrease in the values of morphological features with an increase in the serial number (p < 0.05). The number of panicles on a plant and the number of flowers on a panicle on two callus lines in the second or third group were increased. No variability was detected in five callus lines, i.e., such a phenomenon was not a rule. The nuclear DNA content of doubled haploids in four groups of the same callus line was 1.03– 1.09 pg, and for haploids it was 0.53–0.58 pg. Intracallus variability of nuclear DNA content was detected between groups of haploids of the same line and among doubled haploids of the same line. Significant differences were found between the haploids of one callus line and the three other callus lines of the Sadko × Kuboyar hybrid towards an increase of nuclear DNA content (p < 0.0015). The theoretical possibility of the appearance of intraspecific variability among plants with a small number of chromosomes is considered. A scheme of genomic reorganization is proposed for such species: initial plant (2n) → aneuhaploid plants (n + 1) → megasporogenesis and microsporogenesis of the 0-n type, formation of fertile pollen (n + 1) → diploid plant (2n + 2). Aneuhaploid evolution explains the intraspecific variability of chromosome numbers among plant species with low ploidy. Aneuploid technologies can help in the artificial formation of new polyploid crops, and rice is given a primary role.